Identification and localization of 3-phenylcatechol dioxygenase and 2-hydroxy-6-oxo-6-phenylhexa-2,4-dienoate hydrolase genes of Pseudomonas putida and expression in Escherichia coli. - Khan, A A (1990)
The bphC and bphD genes of Pseudomonas putida involved in the catabolism of polychlorinated biphenyls or biphenyl were identified, localized, and studied for expression in Escherichia coli. This was achieved by cloning a 2.4-kilobase (kb) DNA fragment of recombinant cosmid pOH101 into HindIII site of pUC plasmids downstream of a lacZ promoter and measuring the enzyme activities of 3-phenylcatechol dioxygenase (3-PDase; a product of bphC) and the meta-cleavage product 2-hydroxy-6-oxo-6-phenylhexa-2,4-dienoate hydrolase (a product of bphD). The amount of 3-PDase produced in E. coli was about 20 times higher than that of the enzyme produced by the parent, P. putida. Determination of expression of the bphC and bphD genes through their own promoter sequences or by using the lacZ promoter of pUC plasmids was done by cloning the DNA that encodes bphC and bphD genes in a HindIII site of a promoter selection vector (pKK232-8) upstream of the gene for chloramphenicol acetyltransferase (CAT). The recombinant plasmid (pAW787) constructed by inserting the 2.4-kb DNA in pKK232-8 expressed both 3-PDase and CAT activities. Another hybrid construct (pAW786) in which the DNA insert was cloned in the opposite orientation lacked CAT activity but produced normal amounts of 3-PDase activity. On the basis of these results, we suggest that the bphC and bphD genes were expressed by using promoter sequences that are independent of the promoter that expresses CAT activity in E. coli. The locations of the bphC and bphD genes were determined by insertional inactivation of the open reading frames of structural genes bphC and bphD by Tn5 mutagenesis.(ABSTRACT TRUNCATED AT 250 WORDS)